Analisis Hukum Putusan Mahkamah Konstitusi Nomor 90/PUU/XXI/2023 Tentang Batas Usia Calon Wakil Presiden Di Indonesia - Umam, Muhammad Khoirul (Faculty of Law, Diponegoro University, 2025)
The Constitutional Court Decision No. 90/PUU/XXI/2023 on the age limit for vice-presidential candidates has sparked significant controversy, as it is deemed inconsistent with the principles of constitutionality, separation of powers, and legal justice. The decision introduces a new norm by allowing candidates under 40 years old who have held elected positions, raising questions about the Court’s role as a negative legislator and its impact on Indonesia’s constitutional system. This study formulates three main issues: (1) how constitutionality and justice principles are reflected in the decision, (2) the legal and procedural weaknesses within Indonesia’s constitutional framework, and (3) the implications of the decision for electoral implementation. The research employs normative legal methods with statutory, case, and conceptual approaches, drawing on primary, secondary, and tertiary legal sources. The findings reveal that the decision not only creates discrimination in fulfilling citizens’ political rights but also undermines the Court’s function as the guardian of the constitution. Moreover, legal reasoning inconsistencies, violations of the legal standing principle, and potential conflicts of interest further erode the Court’s legitimacy. In conclusion, Decision No. 90/PUU/XXI/2023 negatively affects legal certainty, democracy, and public trust; therefore, consistent judicial restraint, stronger oversight, and electoral law revisions are required to safeguard constitutional supremacy.